Pengaruh Model Pembelajaran dan Kecerdasan Intelektual Terhadap Hasil Belajar Sejarah Siswa di SMA Negeri 1 Karawang - Indah Megawati (Jurnal Pendidikan Sejarah, 2017)
This research is purpose to find the influence of instructional model and intellegencequotient to history learning outcomes in Senior High School 1 Karawang. This research isquantitative type with use experiment design methode treatment by level 2x2. The instrument whichused to result of history learning is multiple choices test. Besides, intellegence quotient gets by resultof students' IQ test. This test is organized by an institute for IQ test. At that time students' receive inKarawang Senior High School 1. This research's result shows that: (1) result of history learning forstudents who follows learning model Numbered Heads Together ( NHT) is higer than students whofollows conventional learning model. (2) there are interactions between learning model andinttelegence quotient (3) students who follows history learning by use NHT learning model by highintellegence quotient is higer than srudents who follows conventional learning model by highintellegence quotient (4) students' result of history learning who follows NHT learning model bu lowintellegence quotient is lower that students' who follows conventional learning method by lowintellectual.